Autologous organoid co-culture model reveals T cell-driven epithelial cell death in Crohn’s Disease - Hammoudi, Nassim; Hamoudi, Sarah; Bonnereau, Julie; Bottois, Hugo; Pérez, Kevin; Bezault, Madeleine; Hassid, Déborah; Chardiny, Victor; Grand, Céline; Gergaud, Brice; Bonnet, Joëlle; Chedouba, Leila; et al. (Frontiers in Immunology, 2022)
Lympho-epithelial interactions between intestinal T resident memory cells (Trm) and the epithelium have been associated with inflammatory bowel disease (IBD) activity. We developed ex vivo autologous organoid-mucosal T cell cocultures to functionally assess lymphoepithelial interactions in Crohn’s Disease (CD) patients compared to controls. We demonstrate the direct epithelial cell death induced by autologous mucosal T cells in CD patients but not in controls. These findings were positively correlated with T cell infiltration of the organoids. This potential was inhibited by limiting lympho-epithelial interactions through CD103 and NKG2D blocking antibodies. These data directly demonstrate for the first time the direct deleterious effect of mucosal T cells on the epithelium of CD patients. Such ex-vivo models are promising techniques to unravel the pathophysiology of these diseases and the potential mode of action of current and future therapies.